Evolving paradigms in the diagnosis and management of premenopausal women with abnormal uterine bleeding - Yılmaz Aksoy, Mine Senem; Bornaun, Teymur (The European Research Journal, 2024)
Abnormal uterine bleeding (AUB) is a common gynecological complaint among premenopausal women, encompassing a wide range of underlying disorders that complicate diagnosis and management. The evolving paradigms in medical science now incorporate advanced imaging techniques, personalized medicine, and molecular diagnostics to improve the accuracy of diagnoses and the effectiveness of treatment plans. This review examines recent advancements in the diagnostic approach, including the use of transvaginal ultrasonography, hysteroscopy, and biomarker analysis, which have significantly refined the identification of endometrial pathologies. Furthermore, we discuss the shift towards individualized treatment strategies that consider patient-specific factors such as age, reproductive plans, and comorbidities, facilitating tailored therapies. Special attention is given to the role of medical therapies ranging from hormonal treatments to novel non-hormonal drugs, as well as the consideration of minimally invasive surgical options as part of a comprehensive management strategy. By integrating current research findings with clinical practice guidelines, this article aims to provide a synthesized view of the dynamic field of AUB management, proposing a multidisciplinary approach to enhance patient outcomes in premenopausal women.